The Effect Of Planting Time Of Upland Rice (Oryza sativa L.) On Cassava (Manihot esculenta) Intercropping - Lil Khawa, Evicha Zulianur; Suryanto, Agus Suryanto; Nurlaelih, Euis Elih Nurlaelih Elih (Plantropica: Journal of Agricultural Science, 2024)
Cassava (Manihot esculenta) cultivation is often carried out with an intercropping pattern with upland rice (Oryza sativa L.) as an intercrop which is expected to increase production and maximize land use. Cassava and upland rice have the same land characteristics, which are planted on dry land so they are suitable for intercropping. The effort used to make land efficient in this system is to adjust the planting time between intercropping plants and the main crop. The purpose of this study was to determine the effect of planting time of upland rice (Oryza sativa L.) on cassava (Manihot esculenta) intercropping. This research was carried out from May to September 2021 in front of Universitas Brawijaya at Mrican Village, Mojoroto District, Kediri City with a place height of 67-100 meters. The study was conducted using a one factor Randomized Block Design (RBD), which is planting time with a combination of 5 treatments and replications. The treatments used included W1: upland rice planting time 14 days before cassava, W2: upland rice planting time 7 days before cassava, W3: upland rice and cassava planted together, W4: upland rice planting time 7 days after cassava , W5 : planting time of upland rice 14 days after cassava. Data were analyzed using variance (ANOVA), if there was a significant effect it was continued with a follow-up test of Honest Significant Difference (BNJ) at 5% significance level. The most appropriate treatment is planting time for upland rice 14 days after cassava, due to the low competition between cassava and upland rice so that cassava and upland rice yields will remain good.